Introduction of Colonic and Fecal Microbiota From an Adult Pig Differently Affects the Growth, Gut Health, Intestinal Microbiota and Blood Metabolome of Newborn Piglets - Qi, Renli; Zhang, Zhuo; Wang, Jing; Qiu, Xiaoyu; Wang, Qi; Yang, Feiyun; Huang, Jinxiu; Liu, Zuohua (Frontiers in Microbiology, 2021)
Microbiota transplantation is a rapid and effective method for changing and reshaping the intestinal microbiota and metabolic profile in humans and animals. This study compared the different influences of the introduction of fecal microbes and colonic microbes from a fat, adult pig in newborn pigs. Both colonic microbiota transplantation (CMT) and fecal microbiota transplantation (FMT) promoted growth and improved gut functions in suckling pigs up to weaning. FMT was more beneficial for body weight gain and body fat deposition in piglets, while CMT was more beneficial for intestinal health and mucosal immunity. 16S rDNA sequence analysis indicated that both CMT and FMT significantly increased the abundances of beneficial or functional bacteria, such as Lactobacillus and Prevotella_2 genera, in the piglets, and reduced the abundances of harmful bacteria, such as Escherichia-Shigella. Blood metabolome analysis showed that transplantation, especially FMT, enhanced lipid metabolism in piglets. In addition, while CMT also changed amino acid metabolism and increased anti-inflammatory metabolites such as 3-indoleacetic acid and 3-indolepropionic acid in piglets, FMT did not. Of note, FMT damaged the intestinal barrier of piglets to a certain extent and increased the levels of inflammatory factors in the blood that are potentially harmful to the health of pigs. Taken together, these results suggested that intestinal and fecal microbiota transplantations elicited similar but different physiological effects on young animals, so the application of microbiota transplantation in animal production requires the careful selection and evaluation of source bacteria.